Autologous Plasma rich platelet versus Low Molecular weight Hyaluronic Acid in Knee Osteoarthritis - Zahra Hajihashemi; Mohammad Mahdi Emam; Mohammad-Reza Sohrabi (Shahid Beheshti University of Medical Sciences, 2020)
Objective: This study aimed to compare the effect of autologous plasma rich platelet (PRP) versus Low molecular weight Hyaluronic acid (HA) on pain, function and stiffness in knee osteoarthritis during six months follow-up. Design: Through a non-placebo blocked randomized controlled trial with parallel design on 77 patients with knee osteoarthritis; 50 in intervention group, treated by PRP; 27 in control group, treated by HA.  They received three injections and assessed before, after two and six months. Pain, stiffness and function were assessed using WOMAC and VAS. Descriptive statistics, chi-square, and ANOVA were used when appropriate. Results: Pain reduced in both groups compared to their respective baseline (P<0.007); the reduction rates were similar in both groups (P>0.1). WOMAC and VAS scores were different between before injection and both two and six months follow-ups in both groups (P<0.001); although increasing of VAS score between two and six months follow-ups was more considerable in PRP but not statistically significant (P=0.08). Considering Kellgren-lawrence classification of knee osteoarthritis, WOMAC scores were different in patients with grade 2 and 3 in both groups (P<0.01); but VAS scores were different with grade 3 only in PRP group (P=0.009). Conclusions: There was no difference between PRP and HA in reducing symptoms of knee osteoarthritis compare to their baseline but sustainability of the effect may be more with HA.